Muhammad Syahrur's Theory of Limitations as an Effort to Reform Islamic Law - Ayu Juniaty Siregar; Sahdia Tanjung (AT-TAFAHUM: Journal of Islamic Law, 2025)
This study aims to examine the Theory of Limitations proposed by Muhammad Syahrur as an effort to reform Islamic law in facing the dynamics of modern society. This theory offers an interpretive approach that emphasizes the existence of minimum limits (hadd al-adna) and maximum limits (hadd al-a'la) in determining law, thus allowing flexibility in the application of sharia without deviating from the basic principles of the Qur'an. The research method used is a literature study with a qualitative approach, through an analysis of the works of Syahrur and literature related to contemporary Islamic legal thought. The results of the study indicate that the Theory of Limitations makes a significant contribution to the development of a more contextual and adaptive ijtihad methodology to social change. In addition, this theory also opens up space for a reinterpretation of Islamic law that is more responsive to modern issues such as social justice, gender equality, and human rights. Thus, the Theory of Limitations can be seen as an alternative in Islamic legal reform that seeks to bridge the gap between normative texts and empirical reality, without ignoring the fundamental values of Islamic teachings.